2013
DOI: 10.1371/journal.pone.0073582
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Protease Mutations among Patients Failing Second-Line Antiretroviral Therapy and Response to Salvage Therapy in Nigeria

Abstract: BackgroundTo date, antiretroviral therapy (ART) guidelines and programs in resource-limited settings (RLS) have focused on 1st- and 2nd-line (2 L) therapy. As programs approach a decade of implementation, policy regarding access to 3rd-line (3 L) ART is needed. We aimed to examine the impact of maintaining patients on failing 2 L ART on the accumulation of protease (PR) mutations.Methods and FindingsFrom 2004–2011, the Harvard/APIN PEPFAR Program provided ART to >100,000 people in Nigeria. Genotypic resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 30 publications
9
42
0
Order By: Relevance
“…All the patients had preserved susceptibility to DRV/r since it is the only PI drug analysed that was not selected by any resistance mutation. Similar observations had been reported in a more widespread study in Nigeria which examined the impact of maintaining patients on failing second line ART on the accumulation of PR mutations [30]. Isolates in this study also showed high level of susceptibility (96.4%) to SQV/r.…”
Section: Discussionsupporting
confidence: 88%
“…All the patients had preserved susceptibility to DRV/r since it is the only PI drug analysed that was not selected by any resistance mutation. Similar observations had been reported in a more widespread study in Nigeria which examined the impact of maintaining patients on failing second line ART on the accumulation of PR mutations [30]. Isolates in this study also showed high level of susceptibility (96.4%) to SQV/r.…”
Section: Discussionsupporting
confidence: 88%
“…This time is a period of potential accumulation of resistance mutation and transmission of resistant HIV strains. The time between first detectable VL (suspicion of failure) and DRT sample reception in the laboratory was not associated with the presence of major PI mutation in our study, but it has been shown that a long duration of non‐suppressive second‐line may increase this risk . The high work load at the clinic led to difficulties to follow the recommended procedure which was to use SAMBA POC VL results to collect blood samples for DRT on the same day as the second detectable VL.…”
Section: Discussionmentioning
confidence: 61%
“…In future work it would be interesting and important to know whether Gag mutations are capable of facilitating emergence of major protease mutations in prolonged culture conditions under suboptimal drug pressure. This could potentially explain why prevalence of major protease mutations increases over time during PI exposure in clinical studies (43). Next one could perform population dynamics simulations to incorporate RC and susceptibility data in order to model the proportion of resistant and susceptible viruses over time, and possibly therefore predict emergence of major mutations in protease.…”
Section: Discussionmentioning
confidence: 99%